A/R/TOGRAPHY AND TEACHER EDUCATION IN THE 21ST CENTURY - Wiebe, Sean; Caseley Smith, Claire (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2017)
In this article, we summarize research on Prince Edward Island where a Prince Edward Island teacher, identifying as an a/r/tographer, designed a digital and multiliteracies unit, as part of a directed studies course in her Master of Education program. Small in scope, this single participant case study was designed to give a fuller picture to three difficulties teachers often face when teaching new literacies. These are (1) applying multiliteracies theory, (2) thinking across literacies domains, and (3) assessing literacies holistically. Findings are derived from our six research conversations, and our discussion highlights the necessity of artistic ways of being and thinking for teacher education programs in the 21st century. A/R/TOGRAPHY ET LA FORMATION DES MAITRES AU 21e SIECLE Dans cet article, nous résumons les recherches au sein desquelles un enseignant de l’Île-du-Prince-Édouard — s’identifiant comme un a/r/tographe — a créé une unité numérique et multilittéraire dans le cadre d’un cours d’études dirigées d’un programme de maitrise en éducation. Bien que d’ampleur modeste, cette étude de cas s’attardant à un seul participant a été élaborée dans le but de tracer le portrait complet de trois difficultés fréquemment rencontrées par les enseignants lorsqu’ils enseignent de nouvelles littératies. Ces difficultés consistent à (1) appliquer la théorie relative aux multilittératies; (2) adopter un mode de pensée interlittératies et (3) évaluer les littératies de manière globale. Les conclusions sont fondées sur six conversations tenues dans le cadre de la recherche, et notre article met en lumière la nécessité de repenser la formation des maitres au 21e siècle, pour y intégrer des manières artistiques d’être et de réfléchir.